2018
DOI: 10.1016/j.apenergy.2018.06.115
|View full text |Cite
|
Sign up to set email alerts
|

Opportunities for behavioral energy efficiency and flexible demand in data-limited low-carbon resource constrained environments

Abstract: The need for transitioning towards low-carbon energy systems, and the recent boom in available data, allows for a constant re-evaluation of global electricity sector decarbonization progress, and its underlying theoretical assumptions. Arguably, the existing decarbonization literature and institutional support frameworks focus on top-down supply side mechanisms, where policies, goals, access to financing, and technology innovation are suggested as the main drivers. Here, we synthesize eleven global datasets th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 89 publications
0
8
0
Order By: Relevance
“…Further, resistance within organizations to change existing processes, especially if they have been in place for a long time, can impede the adoption of new low-carbon methods. The authors of [24] specified resource constraints as one of the major obstacles to LCM. Limited availability of raw materials or resources for low-carbon manufacturing, especially if they are region-specific, can create challenges in sourcing sustainable inputs.…”
Section: Identification Of Challenges To Lcm Adoptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, resistance within organizations to change existing processes, especially if they have been in place for a long time, can impede the adoption of new low-carbon methods. The authors of [24] specified resource constraints as one of the major obstacles to LCM. Limited availability of raw materials or resources for low-carbon manufacturing, especially if they are region-specific, can create challenges in sourcing sustainable inputs.…”
Section: Identification Of Challenges To Lcm Adoptionmentioning
confidence: 99%
“…• Third, integrating MICMAC analysis enhances the research's depth by categorizing challenges into driving and dependent factors, thereby offering strategic insights into which challenges are pivotal and which are influenced by others. References: de Sousa Jabbour, Chiappetta Jabbour [17]; Ohene, Chan [18]; Shen, Wu [19]; Chen, Zhang [20]; Singh, Jindel [21]; Liu, Wang [22]; Vimal, Kumar [23]; de Leon Barido, Suffian [24]; Sindhwani, Singh [25].…”
mentioning
confidence: 99%
“…Initially, China has invested $6.4billion (b) for coal projects while $8.8b for clean power production. Peters et al, 2017;Peters et al, 2017;and de Leon Barido et al, 2018, have identified that in achieving the global goals energy efficiency play an essential role related to energy security; Bouton et al, 2010;Bouton et al, 2010;and Peters et al, 2017 for economic efficiency and IEA, 2017 for climate change and local pollution reduction. According to Demski et al, 2015, energy security in the form of a reliable, safe, and is affordable for the public.…”
Section: Review Of the Studymentioning
confidence: 99%
“…A study in Nicaragua found that users were willing to sacrifice monthly cash payments for energy consumption information reports that they were able to codesign with researchers. The users then adjusted their usage and reduced consumption to save money accordingly [24]. These energy efficiency benefits can pose a loss-of-revenue risk to utilities using volumetric pricing, but this risk should both be considered small relative to opportunities for increasing the customer base through more resource efficient usage and a challenge that can be addressed by decoupling profits from energy sales.…”
Section: A Technical Datamentioning
confidence: 99%